FEATURES AND STRUCTURE OF THE COMPLICATIONS OF ENDOVENOUS LASER ABLATION - Atamaniuk , O. Yu. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The aim of the research work: to analyze the structure, frequency and features of complications after endovenous laser ablation in patients with varicose veins of the lower extremities. An open, prospective study was conducted, which included 208 consecutive patients with varicose veins of the lower extremities. All patients underwent endovenous laser ablation of varicose veins and investigated the structure and features of the development of postoperative complications. Pathological reflux of blood in the trank of the great saphenous vein of the lower extremity was diagnosed in 206 cases, isolated reflux in the trank of the small saphenous vein was observed in 24 (10.4 %) limbs, in 16 patients EVLA was performed simultaneously in the small and large saphenous veins). One or more adverse events were reported by 94 patients (45.2%) during the first 2 weeks after treatment, and pain was the most common symptom in the study patients, with complaints reported by 82 (39.4 %) patients with a mean value immediately after treatment). The second most common complication of endovenous laser ablation was ecchymosis, which developed in 44 (19.1% extremities). Tissue induration and hyperpigmentation along the coagulated vein were observed in 5.2% and 3.9%, respectively. Manifestations of transient paresthesia and wound infection were observed in 0.4% of cases, in 2 (0.9 %) patients after EVLA in the great saphenous vein. In the postoperative period serious adverse events developed, such as EHIT II and in 3 (1.4 %) cases asymptomatic distal deep vein thrombosis. Endovenous laser ablation is an effective method of treating varicose veins of the lower extremities with a high safety profile. Clear standardization of the procedure and postoperative monitoring will minimize the risks of postoperative complications and eliminate them in a timely manner.